NILAI EKONOMI TANAMAN PALA DI DESA KAUDITAN KABUPATEN KAUDITAN KECAMATAN KAUDITAN - Vicky I. Suluh; Olfie L.S. Benu; Lyndon Pangemanan; Oktavianus Porajouw (Universitas Sam Ratulangi, 2015)
ABSTRACT Vicky I. Suluh. Economic Value of Nutmeg Plant in Kauditan Village, Sub- district Kauditan North Minahasa Regency. Under Guidance Benu L.S Olfie, as a Chairman and Lyndon Pangemanan, and Octavianus Porajouw as members. The objective of this research is to calculate the economics value of the nutmeg plant with a productive life of plants. Range of plants : 8 - 19 years, 20 - 30 years and > 31 years based on the cost calculation and revenue of nutmeg farming according to the current price. Case study is on farmers in Kauditan village, Kauditan Sub distric North Minahasa Regency. This research is conducted for 3 months (November 2012 - January 2013). The source of the data in this study were obtained from primary data and secondary data. The primary data obtained through interviews with farmers based on a list of questions in the form of questionnaires and equipped with secondary data which is obtained from relevant agencies such as the office of the Department of Agriculture of North Minahasa. Methods of data analysis in this research is descriptive analysis using the data collected and presented it in tabular form. The research results showed that the Nutmeg farming with age of plant 8- 19 years with an average 90 productive trees, the average revenue is Rp.43.143.000 and the average of cost is Rp.7.935.333 with a value of R / C ratio is 5,43 and the average economic value Rp.479.366. For plants at the age of 20-30 years with an average number of 75 productive trees, the average revenue is Rp.33.191.667 and the average of cost Rp. 7.733.000 with R / C ratio of 4.29 and average of economic values Rp.442.555 and the plant for age> 31, with 213 productive trees, the average revenue is Rp. 96.000.000 and the average cost of Rp.17.511.000 with a value of R / C ratio is 5.48 and the average of economic value Rp. 450.704. This ratio illustrates that the economic value of each Rp.1,00 expenditure in the nutmeg farm will generate revenue of Rp.5,43 to plant of age 8-19 years. The plants for 20 – 30 years, it generate 4,29 and for the plant > 30 years it generate 5,48 potential revenue. To develope the bussines of farming, every farmer is required to make a detailed of costs and revenues in the form of bookkeeping and role of goverment especially extension agencies to guide farmers to run their farm business.